PREDICTING INDONESIAN CONSUMERS ACCEPTANCE AND USAGE TOWARD AR/VR IN LIVE COMMERCE OF BEAUTY PRODUCTS - Muliadewi, Zakina Putri; Windasari, Nila Armelia; Garnida, Nita (International Journal of Social Service and Research, 2025)
This research aims to address the challenges associated with the application of augmented reality (AR) and virtual reality (VR) in live commerce for cosmetic products, focusing on the perception of consumers in Indonesia who are still very early or still in the awareness stage of the acceptance and/or application of AR/VR technology in online shopping. The study employs a positivist scientific method to systematically investigate the external variables influencing the adoption of AR and VR technologies in the live commerce beauty industry, identifying five significant determinants: Content Relevance, Performance Expectancy, Hedonic Motivation, Personal Innovativeness, Social Media Influence, and Trust. Effort Expectancy and Trust did not significantly affect Behavioral Intention, while Consumer Readiness (CR) positively affected Behavior Intention (BI), indicating that informed consumers are more likely to adopt AR/ VR technologies when exposed to social media influence. The findings suggest several strategies for businesses to enhance consumer adoption, with the goal of converting viewers into buyers. Additionally, developing frameworks to measure the return on investment (ROI) of AR integration in e-commerce could provide valuable insights for businesses, justifying investments and refining strategies for sustainable profitability.